2020
DOI: 10.1016/j.preteyeres.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Persistent remodeling and neurodegeneration in late-stage retinal degeneration

Abstract: Retinal remodeling is a progressive series of negative plasticity revisions that arise from retinal degeneration, and are seen in retinitis pigmentosa, age-related macular degeneration and other forms of retinal disease. These processes occur regardless of the precipitating event leading to degeneration. Retinal remodeling then culminates in a late-stage neurodegeneration that is indistinguishable from progressive central nervous system (CNS) proteinopathies. Following longterm deafferentation from photorecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 222 publications
2
136
1
Order By: Relevance
“…Double immunostaining for pS6 Ser240/244 and calbindin showed a decrease in the number of calbindin-positive tips due to retraction of horizontal terminal fibers caused by photoreceptor loss (Cuenca et al, 2014, Pfeiffer et al, 2020. Moreover, in the rd10 retina half of the remaining horizontal cell terminal tips were devoid of pS6 Ser240/244 labeling ( Fig.…”
Section: Insulin Receptor Expression and Signaling In Wt And Rd10 Retmentioning
confidence: 87%
See 3 more Smart Citations
“…Double immunostaining for pS6 Ser240/244 and calbindin showed a decrease in the number of calbindin-positive tips due to retraction of horizontal terminal fibers caused by photoreceptor loss (Cuenca et al, 2014, Pfeiffer et al, 2020. Moreover, in the rd10 retina half of the remaining horizontal cell terminal tips were devoid of pS6 Ser240/244 labeling ( Fig.…”
Section: Insulin Receptor Expression and Signaling In Wt And Rd10 Retmentioning
confidence: 87%
“…Interestingly, in rd10 retinas INSR downregulation and consequent impairment of INSR signaling coincided with the presence of disconnected but otherwise apparently viable rod terminals. Alterations in retinal synaptic circuitry as part of retinal remodeling during photoreceptor degeneration have been acknowledged for more than two decades (Jones, Kondo et al, 2012, Lewis, Linberg et al, 1998, Pfeiffer et al, 2020, Strettoi, Pignatelli et al, 2003. De-afferentiation of second-order neurons has typically been described in advanced stages of degeneration as a consequence of photoreceptor loss (Jones et al, 2012, Lewis et al, 1998, Pfeiffer et al, 2020, Strettoi et al, 2003.…”
Section: Aav-hpi Treatment In Rd10 Mice Preserves Visual Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent work has demonstrated that retina behaves similarly to CNS with respect to late stage disease with many of the same features observed in retina as in other neuropathies of the brain. 14 These features also make the retina an ideal candidate for mapping neuronal network disruptions that occur as a result of neurological disease by creating connectomes of pathological tissue: Pathoconnectomes. Here, we introduce the structure, features, and initial findings from Retinal Pathoconnectome 1 (RPC1) an open-access, serial-section transmission electron microscopy (ssTEM) connectome volume, generated from a rabbit model of autosomal-dominant conesparing retinitis pigmentosa (RP).…”
Section: Role Of Connectomics In Understanding Neurological Diseasementioning
confidence: 99%